Strategies And Methods Of Learning Arabic Vocabulary/ Strategi Dan Metode Pembelajaran Kosakata Bahasa Arab - S, Febry Ramadani; Baroroh, R Umi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This research aims to analyze strategies and methods of learning Arabic vocabulary that is tailored to the level of students. The research method is library research which is some of the data resources took by books and journals; then researchers analyze the data with content analysis methods. The problem which mostly figured out by students in learning Arabic is their lack knowledge of understanding its vocabulary, the problem which mostly figures out by students in learning Arabic is short of knowledge in vocabulary and understanding its meaning. Those impact to the low skills of students in learning the Arabic language. So, there is a need for vocabulary learning strategies and methods that are appropriate to the level of students. The results found that there were strategies and methods which appropriate to the level of students for the primary level (mubtadi'): (1) the mim-mem method, and (2) the singing method, for the intermediate level (mutawasiá¹): (1) Total Physical Response (TPR) method, (2) effective demonstration method, and (3) direct method, and for advanced-level (mutaqaddim): (1) reading method, and (2) cognitive method.